The impact of low-dose gamma radiation on immune modulation in a mouse model of spontaneous mammary gland tumorigenesis - Khan, Abrar Ul Haq; Blimkie, Melinda; Marr, Bryan; Wu, Jin; Pack, Tyler; Kaczmarek, Shelby; Jo, Dong-Hyeon; Laakso, Holly; Lee, Seung-Hwan (Frontiers in Immunology, 2025)
Understanding the impacts of low-dose ionizing radiation exposure has significant public health implications. However, the effects of low-dose ionizing radiation on immune modulation and cancer progression remain contentious. This study aimed to investigate the impact of chronic low-dose gamma radiation on mammary tumorigenesis and immune homeostasis using a transgenic mouse model. Female MMTV-neu transgenic mice were exposed to continuous whole-body 60Co gamma radiation over a period of 56 days, thereby receiving cumulative absorbed doses of 10, 100 and 2,000 mGy. Mice were analyzed at 3.5, 6 and 8 months of age for changes in immune cell composition and function, as well as tumor development. We found that mice exposed to LDR exhibited transient increases in NK cell frequency, along with improved IFN-γ production following ex vivo stimulation. Notably, the expression of NKG2D on NK cells was upregulated following LDR exposure. Low-dose radiation also modulated inflammatory cytokine profiles and immune cell populations, such as macrophages and myeloid-derived suppressor cells. Despite these immune changes, the overall impact on tumorigenesis was minimal. Although our data indicated that the LDR treatment did not impact survival and cancer progression, the observed results of NK cell proportion, activation and function provide evidence of the stimulatory effects of LDR on NK cells. These findings aim to contribute to health risk assessments and advise radiation protection regulations.